Pemekaran Nagari Tapan : Analisis Dampak Politik, Ekonomi dan Sosial Tahun 1999-2013 - Saputra, Yandi; Utami, Wulandari Nurul; Darmawan, Budi (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to examine the dynamics of the division of Nagari Tapan. The study employs a historical research method, consisting of several stages: heuristics, criticism, interpretation, and historiography, to analyze the development of Nagari Tapan. The findings show that the division was regulated by Government Regulation No. 09 of 2000 concerning the Basic Provisions for the Reorganization of Villages in West Sumatra into nagari administrations. The impact of this policy became evident in 1999 when Nagari Tapan was officially divided into the Basa Ampek Balai Tapan District with a single nagari administration. By 2012, the number of nagari administrations had grown to 20, along with two district governments. This division of nagari was part of an effort to establish new autonomy in Electoral District V (Dapil V), beginning with the division of nagari and districts. Following the division in 2012, significant changes occurred in Tapan, including: first, the growth of local democracy (politics); second, increased economic development; and third, the strengthening of social and cultural values.